Dental Health Education Using gigi.id Application to Elementary School Students in Banjarmasin City - Hermien Nugraheni; Ani Subekti; Endah Ariyanti Ekoningtyas; Prasko Prasko (Jurnal Kesehatan Gigi, 2022)
Background : the most common oral health problem experienced by school-age children is dental caries. The cause of oral problems, one of which is the lack of knowledge of the importance of maintaining oral health. Good knowledge of oral health can be pursued through educational activities, such as counseling using the media, including electronic media in the form of the gigi.id application. Aim : examined the differences in the effectiveness of counseling with the gigi.id application and video playback on the oral health knowledge of elementary school students. Method :this type of research is a quasi-experimental with a cross sectional approach. The normality test of the data was carried out using Kolmogorov-Smirnov and then analyzed using Pair T-test. The effectiveness between media is compared using One Way Anova. The test was continued using the Independent T-test to determine the difference in effectiveness between pairs of extension methods.Result : there was a significant difference with p0.05 in counseling using the gigi.id application media and using lectures. The results of the different test on video playback media did not show a significant difference. The results of the effectiveness test showed that there was a significant difference between methods with p0.05, which was 0.000.The test of differences in effectiveness between pairs of counseling methods, showed a significant difference with p0.05 in counseling couples with video playback and the application of gigi.id, as well as counseling of the lecture method and application of gigi.id.Conclusion : counseling using the gigi.id application is more effective than video playback in increasing students' dental and oral health knowledge